Cómic informativo turístico sobre una leyenda urbana para promover la cultura y tradición ecuatoriana. - Tapia Quingaguano, Anthony Alexander (2025)
This research project proposes the creation of an informative tourist comic based on the urban legend of Carmelita León (the witch of Riobamba), with the aim of promoting and preserving Ecuadorian culture and traditions. This proposal arises in response to the progressive loss of intangible cultural heritage, especially among younger generations, due to the influence of globalized cultural trends. The importance of this project lies in offering an innovative alternative to strengthen cultural identity and spread the value of heritage through an accessible and attractive medium. The comic is conceived as a visual, accessible, informative, touristic, and educational tool that integrates narrative and illustrative elements, creating a bridge between the cultural past and present communication. Using a qualitative approach, the relationship between graphic design, cultural tourism, and visual narrative was analyzed as an effective means of rescuing traditions and strengthening cultural identity. To this end, a local urban legend from the city of Riobamba was selected as the basis for developing an illustrated narrative that, in addition to informing, would awaken tourist and cultural interest among both the local population and national and foreign visitors. During the analysis and interpretation of the qualitative data, the information collected was organized, coded, and synthesized. As a result, patterns, thematic categories, and conceptual relationships were identified that enriched the theoretical and visual proposal of the comic. The results show that the use of comics as an informational tourism product facilitates the understanding of cultural content and promotes the appropriation of national identity. It also allows for the diversification of Ecuador’s tourism offerings through innovative resources that strengthen the sense of belonging and promote respect for intangible heritage, leading to the conclusion that comics, as a visual and playful tool, have great potential as a means of cultural dissemination and tourism promotion.